Studies On Effect Of Laser-Wood Interactions Of Some Malaysian Hard Woods - Jaafar, Nor Fadhlin (2007)
The CO2 laser produces a beam of infrared light with the principal wavelength bands between 9.4 fJm and 10.6 pm. In this study, 10.6 um is used to correlate the CO2 laser with balau, gerutu, kempas, kekatong, keledang, jati, kelat and nyatoh. By lasing at different settings of pulse width modulation (PWM), duration of laser exposures and distances from laser source to these hardwood samples, the surface diameters and depth penetrations of the burned portions of the wood is evaluated using x-ray and ultrasonic methods. Besides, elements in valuable hardwoods also been obtained by scanning microscope electron (SEM). It shows that the power of laser varied linearty with PWM and independent of distances from laser source to wood samples and duration of laser exposure. For fine cutting purpose, the settings are also different for each hardwood samples, depending on the wood density and its structure. Carbon Is the main element in wood because it has the highest atomic percentage among other elements.